Aplicación de una auditoría financiera a la Cooperativa de transporte interprovincial de pasajeros “Macuchi,” en el cantón La Maná, provincia de Cotopaxi, en el periodo 1 de enero al 31 de diciembre del 2012 - Molina Núñez, Mónica Elizabeth (2014)
The financial audit is the total or partial analytical review of an organization with the purpose of knowing the level of performance and outline opportunities of improvement to innovate and create a sustainable competitive advantage. In the Cooperative of transport “Macuchi”, a financial audit has not been done which produces that administrative errors continue, delaying the administrative and financial management of the institution and with this background was feasible to implement the Financial Audit in the Cooperative of transport “Macuchi” for which it began from the collection of information based on the operationalization.